Meritocracia y desempeño en la carrera del servicio público en la Municipalidad Distrital de Indiana 2021 - Chota Doli, Fernando (2022)
The research presented had as a general objective to determine the relationship between meritocracy and performance in the public service career in the District Municipality of Indiana, 2021; Also, a descriptive study - correlational and non-experimental design has been chosen, from which a sample of 32 public servants has been taken, who were surveyed through a questionnaire. From which, the following results were obtained that, the meritocracy is very adequate (28%) because the selection process is almost always carried out on the basis of merit, in addition, the training process always strengthens capacities, on the other hand, almost specializations are never developed to obtain the academic degree. Likewise, career performance is rated as optimal (38%), since the servers always participate in the institutional plan, also, the servers almost always show consideration and appreciation for the staff, on the other hand, they always show a level of self-esteem adequate, in the same way they almost always show a proactive attitude and, finally, they always prepare management documents to fulfill assigned functions. Finally, the research concludes that meritocracy is related to career performance in a considerable and significant way with (rho = .868; sig. = 0.000); The same happens with the incorporation to the civil service (rho = .521; sig. = 0.002); The same happens with training management (rho = .876; sig. = 0.000); and performance management (rho = 716; sig. = 0.000).